Pengaruh Citra Toko, Kualitas Yang Dirasakan, Dan Kepercayaan Nilai Yang Dirasakan Terhadap Niat Beli Konsumen Di “Hasanah Bakery & Cakes” Cabang Kerasaan - Melati sitorus; Juraeni Juraeni; Dinda Dinda; Dinda Hafifa (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Purchase intention is difficult to achieve because of the influence of someone buying a product. A product must have advantages over other products so that consumers are interested in the product. The development of the business world is inseparable from this kind of competition, and companies need to continue to innovate in order to survive.This study aims to determine the role of store image, perceived quality, and perceived value trust in consumer purchase intention at hasanah bakery & cakes Kerasaan branch.Research Questionnaires were distributed at the hasanah bakery & cakes store within 1 week. To achieve this, it is necessary to go to the respondents and analyze whether they meet the given criteria.a. Based on the tcount value obtained from each variable, it can be seen that the independent variables, namely those consisting of Store Image, Perceived Quality, Value Trust funds partially have a significant influence on the dependent variable, namely Hasanah Bakery & Cakes Purchase Intention in Kerasaan. So that the hypothesis that the researcher proposes is proven to be true. b. Based on Fhitung Store Image, Perceived Quality, and Trust Niali simultaneously have a significant influence on the dependent variable, namely Hasanah Bakery & Cakes Purchase Intention in Kerasaan. So that the hypothesis that the researcher proposes is proven to be true.